SONO-ELECTROCHEMISTRY - THE OXIDATION OF BIS(CYCLOPENTADIENYL)MOLYBDENUM DICHLORIDE - Compton, R; Eklund, J; Page, S; Rebbitt, T (1995)
The oxidation of [Mo(cp)2Cl2] (cp = η-C5H5) in acetonitrile solution at platinum electrodes has been studied. In the absence of ultrasound a simple one-electron oxidation with a half-wave potential of +0.5V (vs. saturated calomel electrode) is observed together with a much smaller wave with a half-wave potential of +1.05 V. In the presence of ultrasound the first wave involves the passage of greater than one electron per molecule of electroactive species and the second wave disappears. The mechanism in equations (i)-(iii) is proposed to explain the observations, where the chemical (c.) (e. = electrochemical) and the disp. (disproportionation) steps are promoted by ultrasound. e. step [Mo(cp)2Cl2] - e- → [Mo(cp)2Cl2]+ (i), c. step [Mo(cp)2Cl2]+ + MeCN → Cl. + [Mo(cp)2Cl(MeCN)]+ (ii), disp. step [Mo(cp)2Cl2]+ + [Mo(cp)2Cl(MeCN)]+ → [Mo(cp)2Cl(MeCN)]2+ + [Mo(cp)2Cl2] (iii).